Abordagem experimental da força de atrito em aulas de Física do Ensino Médio - Monteiro, Isabel Cristina de Castro [UNESP]; Gaspar, Alberto [UNESP]; Monteiro, Marco Aurélio Alvarenga [UNESP] (Universidade Federal de Santa Catarina (UFSC), 2012)
In this paper we propose and describe the performance of an experimental activity to address the concept of friction in High School Physics practical classes. We use a low-cost and simple construction device that enables the determination of the coefficient of static friction between two materials through three different procedures. The results were coherent, with small percentage deviation, which gives reliability to the activity and can stimulate discussions in class. The activity also allows greater contextualization of concepts that are usually discussed only theoretically, requiring a higher abstraction level of the students. This can stimulate discussions and greater interaction between teacher and students.

Neste trabalho, propomos e descrevemos a realização de uma atividade experimental para abordar o conceito de atrito em aulas práticas de Física do Ensino Médio. Utilizamos um equipamento de simples construção e de baixo custo que possibilita a determinação do coeficiente de atrito estático entre duas superfícies por meio de três procedimentos distintos. Os resultados obtidos foram coerentes entre si, com pequeno desvio percentual, o que confere confiabilidade à atividade. A atividade também permite uma maior contextualização de conceitos que normalmente são abordados apenas de forma teórica, exigindo um nível maior de abstração dos alunos, o que pode estimular as discussões e uma maior interação entre professor e alunos.
Keywords: Physics teaching; Friction force; Experimental activity; Ensino de física; Força de atrito; Atividade experimental